2004
DOI: 10.1080/01140671.2004.9514278
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of potato(Solanum tuberosum)cultivars with acry1Ac9 gene confers resistance to potato tuber moth(Phthorimaea operculella)

Abstract: Eight potato (Solanum tuberosum) cultivars were transformed with a modified cry 1AC9 gene under the transcriptional control of the CaMV 35S promoter using Agrobacterium-mediated transformation with a nptII gene conferring kanamycin resistance as a selectable marker. Initially the transformation efficiency of two Agrobacterium strains (LBA4404 and AGL1) were compared using the potato cultivars 'Iwa' and 'Ilam Hardy'. Both strains resulted in similar numbers of regenerated shoots, but there was a higher proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…In potato, it is often desirable to couple high-level expression of the transgene in foliage with no expression in tubers. Constitutive promoters have been used to drive cry gene expression in all previous studies targeting PTM resistance in transgenic potatoes (Douches et al, , 2002Jansens et al, 1995;Cañedo et al, 1999;Li et al, 1999;Chakrabarti et al, 2000;Mohammed et al, 2000;Davidson et al, 2002Davidson et al, , 2004. Since PTM generally infests foliage of potato crops prior to the tubers (Foot, 1979), preventing foliar infestation may be sufficient to avoid tuber infestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To contribute an additional component to integrated pest management, the development of transgenic potatoes that express genes encoding insecticidal compounds has been investigated (Meiyalaghan et al 2005). The use of cry genes from the soil bacterium, Bacillus thuringiensis, has been especially successful (e.g., Jansens et al 1995;Douches et al 1998;Li et al 1999;Davidson et al 2002Davidson et al , 2004Meiyalaghan et al 2006). However, the transfer of native cry genes to plants has often resulted in inadequate gene expression.…”
Section: Introductionmentioning
confidence: 99%